UJI MANOVA UNTUK MENGETAHUI PENGARUH PEMEKARAN WILAYAH TERHADAP PERKEMBANGAN JUMLAH AREA TERBANGUN PERMUKIMAN (STUDI KASUS DI KOTA KOTAMOBAGU SULAWESI UTARA) - Ani Apriani (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2016)
It is certain that area expansion has consequences on the growth of the urban population, as also the migration of people to the center of city which will certainly increase the pressure on land use for the development of infrastructure and basic urban infrastructure. The most evident is in the increase of residential building as a result of migration to the center of city and the number of people.The purpose of this research is to determine the influence of area expansion toward the development of built settlement area in Kotamobagu, North Sulawesi. This research uses quantitative method with pre-experimental and by using one-group pretest-posttest design. It uses multivariate analysis of variance (MANOVA).Based on the result of the analysis of the influence of area expansion, it gives significant influence toward variables: the number of the house, banking, government office, education center, health center, and also worship place. And, the expansion does not give significant influence toward market